Implementation challenges of community-based total sanitation in wetland areas: a case study from Tanjung Jabung Barat - Widya Ayu Pratiningsih; Supriyati; Mubasysyir Hasanbasri (Berita Kedokteran Masyarakat, 2024)
Purpose: Community-Based Total Sanitation or STBM is an empowerment-based approach promoting hygienic behavior without subsidies. However, implementation in geographically challenging areas, such as wetlands, remains problematic, with limited research on context-specific adaptations. This study aimed to analyze the implementation of STBM in wetland areas by examining implementation protocols, monitoring mechanisms, and post-Open Defecation Free (ODF) sustainability in Tanjung Jabung Barat Regency, Indonesia. Methods: This qualitative case study employed purposive sampling to select 12 key informants across multiple sectors (health department, public works, primary health centers, village officials, and community members). Data were collected through in-depth interviews (25 to 80 minutes), participant observation, and document review. Thematic analysis, employing open coding, was conducted with source triangulation to ensure validity. Results: STBM implementation remains focused on Pillar 1 (Stop Open Defecation) with uneven achievement across subdistricts (ODF declaration in only 16.4% of villages despite 74.6% being triggered). Key implementation barriers included: (1) absence of village facilitators and formal STBM working groups; (2) weak post-triggering monitoring systems lacking formal community-to-health center reporting mechanisms; and (3) geographic constraints with conventional sanitation technologies proving unsuitable for wetland conditions. Additionally, a subsidy-oriented community culture hindered the adoption of behavior change. Conclusion: Effective CLTS implementation in wetland areas requires context-specific adaptations, including strengthened village-level institutions, locally adapted sanitation technologies, and formal post-ODF regulations. These findings contribute to understanding the geographical determinants of sanitation program effectiveness and highlight the importance of place-based approaches to achieve sustainable sanitation goals.